Unusual accident during proximal ventricular shunt catheter removal in an infant: a case report - Sousa Barbosa, Gabriele; Freitas Santana, Marília; Moreira Ferreira, Lara; Nogueira Pinheiro, Maria Suelly; de Jesus Silva, Rondineia; Carvalho de Brito de Souza, Liane; Aspilicueta Pinto Filho, Washington; Barros Jucá, Carlos Eduardo (Brazilian Journal of Case Reports, 2022)
Hydrocephalus is a common condition of accumulation of cerebral spinal fluid in the ventricular system. Generally, infants show with progressive macrocephaly or signs and symptoms of intracranial hypertension. The ventricular shunt represents a common and important treatment of hydrocephalus. However, it can occur some complications. The authors report a case of an accident of catheter removal in an infant, which the choroid plexus was removed by accident, and discuss how to diagnose and how to prevent it.